Handbook of home health standards : quality, documentation, and reimbursement - Marrelli, Tina M. (St. Louis, Missouri : Mosby Elsevier, 2012)
Home care clinicians everywhere depend on "the little red book" for essential, everyday information: detailed standards and documentation guidelines including ICD-9-CM diagnostic codes, current NANDA-I and OASIS information, factors justifying homebound status, interdisciplinary goals and outcomes, reimbursement considerations, and evidence-based resources for practice and education. COmpletely revised and updated, this indispensable handbook now includes the most recently revised Federal Register Final Rule and up-to-date coding guidelines.
A unique specialty -- Clinical practice in home care -- OASIS : an overview -- Evaluating clinical practice -- Summary -- Care of older adults : a template for quality care -- Cardiovascular system care -- Endocrine system care -- Gastrointestinal system care -- Genitourinary/renal system care -- Hepatobiliary and pancreatic system care -- Infection and immunologic system care -- Integumentary system care -- Musculoskeletal system care -- Neurologic system care -- Oncologic/hematologic system care -- Psychiatric/psychosocial system care -- Pulmonary/respiratory system care -- Hospice and palliative care -- Acquired Immune Deficiency Syndrome (AIDS) (Care of the child with) -- Antepartal care -- Cancer (Care of the child with) -- Cesarean section (C/S) postcare -- Cystic fibrosis (Care of the child with) -- Diabetes (Care of the child with) -- Gestational diabetes -- Medically fragile child care -- Newborn care -- Postpartum care -- Sickle cell anemia (Care of the child with) -- Surgical (postoperative) care of the child -- Coverage of services -- Key home healthcare definitions -- Key home healthcare abbreviations -- Do not use abbreviations -- Directory of evidence-based and other resources -- Home Care clinical journals and newsletters.
Includes bibliographical references and index.
Keywords: HOME CARE SERVICES -- STANDARDS -- HANDBOOKS, MANUALS, ETC